Directions for surgical capacity developments in Nepal: a population‐based assessment. Issue 9 (6th August 2019) - Knulst, Arjan J.; Gupta, Shailvi; Groen, Reinou S.; Maharjan, Dipak; Kapendra, Amatya S.; Dankelman, Jenny; Kushner, Adam L.
Abstract: Objectives: Lack of access to safe surgery is seen as a major issue that needs to be addressed. The aim of this study was to understand which combinations of factors relate to high occurrences of unmet needs and disability in Nepal, and consequently, how to focus future work to maximise impact in this country. Methods: A large population‐based survey was conducted in Nepal in 2014 to evaluate the unmet surgical needs that result in disability. Recorded factors included diseased anatomical areas, disease specifics, disease locations, injury types, reasons for having an unmet need and the types of disability. Results: Included in the study were 2695 individuals. The anatomical areas facing the highest disabling unmet surgical need were Head (3.9% of population), Groin/Genitalia (2.2% of population) and Extremities (3.6% of population). Four focus areas could be defined. Increase affordability, availability and acceptability of surgical care to non‐traumatic disabling conditions of (i) the eye, and (ii) extremities, and (iii) to traumatic disabling conditions of extremities and finally (iv) increase acceptability of having surgical care for non‐traumatic conditions in the groin and genital area. For the latter, fear/no trust was the main reason for receiving no surgical care despite the resulting shame. Conclusions: This study defined four focus areas that showed the largest unmet needs that resulted in a perceived disability. For those areas, affordability, availability and acceptability of surgical need to be addressed through technical developments, capacity building and raising awareness. Abstract : Objectifs: L'absence d'accès à une chirurgie sûre est considérée comme un problème majeur à résoudre. Le but de cette étude était de comprendre quelles combinaisons de facteurs étaient liées aux besoins non satisfaits et aux incapacités au Népal, et par conséquent, comment cibler les travaux futurs pour maximiser l'impact dans ce pays. Méthodes: Une vaste enquête de population a été menée au Népal en 2014 pour évaluer les besoins chirurgicaux non satisfaits qui entraînent une incapacité. Les facteurs enregistrés comprenaient les zones anatomiques, les spécificités, les localisations de la maladie, les types de blessures, les raisons pour lesquelles les besoins n'étaient pas satisfaits et les types d'incapacité. Résultats: 2695 personnes ont été incluses dans l'étude. Les zones anatomiques impliquées dans des besoins chirurgicaux les plus invalidants étaient les suivantes: tête (3, 9% de la population), aine/organes génitaux (2, 2% de la population) et extrémités (3, 6% de la population). Quatre domaines cibles d'intervention pourraient être définis. Premièrement, augmenter l'accessibilité financière, la disponibilité et l'acceptabilité des soins chirurgicaux aux affections invalidantes non traumatiques de 1) l'œil, 2) des extrémités et 3) aux affections traumatisantes des extrémités, et enfin 4) augmenter l'acceptabilité des soins chirurgicaux pour les affections non traumatiques dans l'aine et les parties génitales. Pour ces derniers, la crainte/l'absence de confiance était la principale raison de ne pas recevoir de soins chirurgicaux malgré la honte qui en résultait. Conclusions: Cette étude a défini quatre domaines cibles d'intervention qui ont montré les besoins non satisfaits les plus importants ayant entraîné une incapacité perçue. Pour ces domaines, il convient de prendre en compte le caractère abordable, la disponibilité et l'acceptabilité des interventions chirurgicales par le biais de développements techniques, d'un renforcement des capacités et la sensibilisation.